Pengembangan Sistem Informasi Digital Zoonosis Melalui Pendekatan Web Semantik - Noviyanti, Komang Kartika; Astuti, Luh Gede; Rahayuda, I Gede Surya; Muliantara, Agus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 4 (2024): JELIKU Volume 12 No 4, May 2024DO - 10.24843/JLK.2024.v12.i04.p17, 2024)
Bali Province with a population of 44,426,000 in 2023, faces challenges in ensuring sufficient food supply. Zoonotic diseases, which can be transmitted from animals to humans, pose a serious and underreported threat, affecting both animal production and human health. To address these challenges, the web-based application Healthy Zoonosis was developed, providing comprehensive digital information on animal diseases, including zoonoses and non-zoonoses, in Bali from 2015 to 2022. The application features browsing, search, and a dashboard for viewing overall disease data. The research utilized Design Science Research Methodology (DSRM) and Mentontology for ontology modeling, with Prototyping for application design. Evaluation involved 17 Participants for ontology validation, yielding a 100% valid result, and 50 Participants for usability testing, scoring 87.3 on the System Usability Scale (SUS). The app not only demonstrates accuracy and validity but also signifies a shift in animal disease prevention paradigms. It is hoped that this application will enhance public understanding of animal health and support proactive government measures in addressing animal disease challenges.